Hubungan Pijat Bayi dengan Frekuensi Menyusu pada Bayi Usia 1-6 Bulan di Puskesmas Lambai Kabupaten Kolaka Utara - Sahari Bulan; Sri Maryanti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Baby massage is a form of multisensory stimulation that involves touch, movement, as well as auditory and visual stimuli, which is known to provide various physiological and psychological benefits for babies, including increased breastfeeding frequency. This study aims to determine the relationship between infant massage and the frequency of breastfeeding in babies aged 1–6 months in the working area of the Lambai Health Center, North Kolaka Regency. The type of research used is an analytical survey with a cross-sectional approach. The sampling technique was carried out in total sampling, involving the entire population of infants aged 1–6 months who met the inclusion criteria. Data collection was carried out through observation and structured interviews with infant mothers, as well as recording breastfeeding frequencies before and after infant massage interventions. Data analysis uses relevant statistical tests to test the relationships between variables. The results showed a significant relationship between infant massage and increased breastfeeding frequency, with a p-value of 0.000 (p < 0.05), indicating that infant massage had an effect on increasing breastfeeding activity in infants. The conclusion of this study is that infant massage has a positive relationship with the frequency of breastfeeding in infants aged 1–6 months. These findings support the use of infant massage as a simple but effective intervention in supporting breastfeeding success, especially in the early stages of life. This study recommends that the practice of infant massage can be socialized more widely to health workers and parents as part of the promotion of maternal and child health. The implementation of regular baby massage has the potential to improve the nutritional status and optimal growth and development of the baby.